Gadget Use and Its Impact on the Social Behavior of Elementary School Students: Penggunaan Gawai dan Dampaaknya Terhadap Perilaku Sosial Peserta Didik di Sekolah Dasar - Sunarsih, Tiwik; Sukartiningsih, Wahyu; Raharjo, Resdianto Permata (Universitas Muhammadiyah Sidoarjo, 2025)
The research used includes quantitative sample collection and data analysis using statistical methods. The research results show that the use of gadgets has a significant impact on students' social behavior, both positively and negatively. The role of parents is also important in controlling students' social behavior, through mentoring, inviting them together, and controlling the use of gadgets. The impact of using gadgets on students' social behavior can vary depending on how they are used and related factors. Therefore, this research suggests the importance of developing strategies to manage and control students' gadget use, as well as involving the role of parents in the education process and student character development.